Global trends in Trichoderma secondary metabolites in sustainable agricultural bioprotection - Cortez-Lázaro, Anthony Apolinario; Vázquez-Medina, Pedro James; Caro-Degollar, Edson Max; García Evangelista, Jennifer Valeria; Cortez-Lázaro, Ronald Alexis; Rojas-Paz, Jorge Luis; Legua-Cardenas, Jose Antonio; Fernandez-Herrera, Fredesvindo; Pesantes-Rojas, Carlos Roberto; Ocrospoma-Dueñas, Robert William; Oliva-Cruz, Segundo Manuel; Manes-Cangana, Gabriel Alberto; et al. (Frontiers in Microbiology, 2025)
The use of Trichoderma spp. constitutes a promising biotechnological strategy for sustainable agriculture, owing to its capacity to control phytopathogens and to produce bioactive secondary metabolites. This study, one of the first of its kind, addresses the absence of a comprehensive bibliometric assessment in this field. A systematic bibliometric analysis was conducted on 235 publications indexed in Scopus (2000–2025). Advanced tools such as VOSviewer and Bibliometrix were employed to track publication trends, identify key research themes, map collaborative networks, and assess the influence of leading authors and institutions. An exponential increase in scientific output was observed, peaking in 2023. Four principal research clusters were identified: antifungal activity, gene regulation, secondary metabolite production, and biosynthesis. India and China accounted for the highest publication volume, while Italy, represented by authors such as Francesco Vinale, accounted for the greatest scientific impact. International collaboration was extensive, particularly between Asia and Europe. The analysis indicates a progression from applied biocontrol studies to research focusing on molecular and genetic mechanisms, highlighting the need for multidisciplinary approaches that integrate biotechnology, agronomy, and microbial ecology. This bibliometric study provides an overview of Trichoderma secondary metabolites in agricultural biocontrol and outlines a research agenda emphasizing field validation, interdisciplinary collaboration, and the adoption of innovative technologies to bridge the gap between research and on-farm application in sustainable agriculture.